Epley’s Maneuver Alone Vs. Epley’s Maneuver with Betahistine for Mild“Paroxysmal Positional Vertigo” A Tertiary Care Hospital Study - Muhammad Ali, Tanveer, Arshad Saeed Awan, Azam Khan, Ali Zaki, Muhammad Mudassir (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: This study aimed to compare the effectiveness of Epley’s and Epley’s maneuvers plus betahistine for treating benign paroxysmal positional vertigo in a Peshawar tertiary care hospital. Method: The study took place from January 15th, 2018, to January 15th, 2019, at a tertiary care hospital for evaluation. There are two types of patients we are aiming for. In group A, patients with benign paroxysmal positional vertigo underwent Epley’s technique alone, whereas those in group B received both the procedure and betahistine. Results: Forty-seven participants participated in the research. There were 15 women in Group A (60%) and ten men (10%) in Group B (55%-45%). Patients had a mean age of 35 years. The combination of Epley’s maneuver and betahistine was more successful than either treatment alone Group B had a 75% success rate in treating benign paroxysmal positional vertigo. In contrast, Group A had a 60% success rate. Conclusion: “Epley’s” operation solitary is effective for treating benign paroxysmal positional vertigo, but when combined with betahistine, the results are much better. Keywords: Benign paroxysmal positional vertigo, “Epley’s” manoeuvre, “Epley’s” manoeuvre + “betahistine”.